2012
DOI: 10.1152/ajpgi.00077.2012
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TNFAIP3 in intestinal epithelial cells protects from DSS- but not TNBS-induced colitis

Abstract: Intestinal epithelial cells (IEC) maintain gastrointestinal homeostasis by providing a physical and functional barrier between the intestinal lumen and underlying mucosal immune system. The activation of NF-κB and prevention of apoptosis in IEC are required to maintain the intestinal barrier and prevent colitis. How NF-κB activation in IEC prevents colitis is not fully understood. TNFα-induced protein 3 (TNFAIP3) is a NF-κB-induced gene that acts in a negative-feedback loop to inhibit NF-κB activation and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…In addition, we found that v-TNFAIP3 mice are protected from DSS-induced IEC death and colitis but not from TNBS-induced colitis (33). This suggested that IEC might play distinct roles in T cell-mediated colitis that are regulated by epithelial expression of TNFAIP3.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…In addition, we found that v-TNFAIP3 mice are protected from DSS-induced IEC death and colitis but not from TNBS-induced colitis (33). This suggested that IEC might play distinct roles in T cell-mediated colitis that are regulated by epithelial expression of TNFAIP3.…”
Section: Resultsmentioning
confidence: 77%
“…Histological examination was performed on tissue fixed in 10% formalin, paraffin embedded, and sectioned longitudinally. Sections (5 m) were stained with hematoxylin and eosin and scored by a pathologist blinded to the genotype using previously described criteria (33).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations